Edukasi Penggunaan Antibiotik Dan Peduli Resistensi Antibiotik Pada Masyarakat Kota Padang - Surya, Sara; Putri, Lusia Eka; Usman, Hendrizal; Nofrizal, Nofrizal; Dwinatrana, Khiky; Kamal, Sefrianita (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2023)
Antibiotics are drugs used to prevent and treat infections caused by bacteria. People mistakenly assume that antibiotics cure all diseases and are not careful in consuming or providing complete antibiotic therapy. Inappropriate use of antibiotics can increase medical costs because resistance makes the drugs more toxic. This Community Service activity aims to provide knowledge about the proper and correct use of antibiotics, providing knowledge about antibiotic resistance. This service activity is carried out by providing education and also providing leaflets about the use of antibiotics and antibiotic resistance. This activity was carried out by GOR H. Agus Salim, Padang City. The results of the activity where the number of participants was 80 people, there were still some who did not understand how to use drugs and antibiotic resistance. The activity was carried out by 6 lecturers assisted by 6 students from the Pharmacy Study Program at Dharma Andalas University. From this service activity, it is hoped that the people of Padang City will receive education about the use of antibiotics and be aware of the dangers of antibiotic resistance.